Bordering on history : rewinding in past in Don DeLillo's Underworld - Brlek, Tomislav (2000)
Don DeLillos novel Underworld presents the reader with a variety of transgressions of the text-context and fact-fiction boundaries, foregrounding the mechanisms of constructing both the past and the present reality and exposing the problem of fictional referentiality. Its two basic moves are the narrative strategy of arranging groups of events in a chronologically reversed order, while simultaneously advancing the plot, and the procedure of invariably selecting the otherwise concealed, obscured, ignored or latent aspects of narrated events, whether fictional or historical. The resulting text the fundamental aporia of its enterprise being emphasised by the novels ruling metaphor and intertextual signal: waste could be read as taking its clue from Wittgenstein: The poet must always be asking himself: is what I am writing really true then? which does not necessarily mean: is this how it happens in reality?
Projekt MZOS
ENG